Reticular drusen in eyes with high-risk characteristics for progression to late-stage age-related macular degeneration. Issue 9 (20th March 2015) - Steinberg, Julia S; Göbel, Arno P; Fleckenstein, Monika; Holz, Frank G; Schmitz-Valckenberg, Steffen
Abstract : Background/aims: To analyse appearance, development over 2 years and characteristic patterns of reticular drusen (RDR) in eyes with high-risk characteristics for progression to late-stage age-related macular degeneration (AMD) (age-related eye disease study stages 3 and 4). Methods: 98 eyes of 98 patients (median age 73.4 years, IQR [69–78]) participating in the Molecular Diagnostic of Age-related Macular Degeneration study were included. Simultaneous combined confocal scanning laser ophthalmoscopy (cSLO) and spectral-domain optical coherence tomography (SD-OCT) imaging as well as colour-fundus imaging was performed at baseline and at 24 months. Two independent graders determined the presence of different RDR phenotypes (cSLO modalities: 'dot', 'target', 'ribbon'; SD-OCT: 'spike' and 'wave') at both visits. Results: At baseline, RDR were detected in 44% (κ 0.96). They were always visible in near-infrared reflectance images. Detection rate was 42% using fundus autofluorescence (FAF), 39% on SD-OCT (waves: 100%; spikes: 90%) and 26% on blue reflectance (BR). 'Dots' were more frequently detected in all imaging compared with 'targets'. The 'ribbon' pattern was most frequently observed in colour images, BR images and FAF images. In 8 of the 48 eyes with no signs of RDR in any imaging modality at baseline, the development of RDR lesions was observed at 24 months (16.6%, κ 0.42). Conclusions: Careful and meticulous analysis using three-dimensional in vivo imaging reveals distinct characteristic RDR patterns underlying detectable dynamic changes over a period of 2 years. RDR in eyes with early or intermediate AMD are a common observation but appear to be overall less common compared with eyes with geographic atrophy.